Structural characteristics of the bovine leukemia virus genome: A mini review - O. Yu. Fomenko (Пищевые системы)
Enzootic bovine leukemia is an infectious disease with a chronic course caused by an RNA‑containing virus of the genus Deltaretrovirus. Despite the implementation of various programs for the elimination of leukemia, the disease is still widespread on the planet and continues to cause significant economic damage. A large proportion of BLV‑infected cattle remain to be asymptomatic carriers of the virus, which complicates diagnosis and contributes to the spread of the disease in the herd. The structure of the BLV genome is generally typical of retroviruses. It consists of genes encoding structural proteins, viral enzymes and regulatory elements flanked on both sides by identical long terminal repeats. The enzyme and structural protein coding genes (gag, pro, pol, and env) play a crucial role in the life cycle of the virus, influencing its infectivity and virion production. The tax and rex regulatory genes regulate viral transcription, export of transcripts from the nucleus to the cytoplasm, and disease progression. The increase in the number of copies of proviral DNA occurs mainly not due to the functioning of the virus reverse transcriptase, but because of clonal reproduction of the affected subpopulations of B‑cells, mainly CD5+ IgM+. This feature provides increased genetic stability of the BLV virus. These properties of the viral genome allow the development of a variety of PCR test systems. The widespread implementation of such systems enables the detection of carriers of the disease at early stages, which should contribute to the effective implementation of national programs to eradicate bovine leukemia.